To solve the given system of equations by elimination, we first rewrite the equations for clarity:
- \( 12x - 3y = 8 \) (Equation 1)
- \( 6x - 1.5y = -16 \) (Equation 2)
We can eliminate the decimals in Equation 2 by multiplying the entire equation by 2:
\[ 2(6x - 1.5y) = 2(-16) \] This gives us: \[ 12x - 3y = -32 \quad (Equation 3) \]
Now, we have the following two equations:
- \( 12x - 3y = 8 \) (Equation 1)
- \( 12x - 3y = -32 \) (Equation 3)
Next, we notice that both equations 1 and 3 have the same left-hand side \( (12x - 3y) \). This gives us:
\[ 8 = -32 \]
This statement is clearly false.
Since the system leads to a contradiction, it implies that there is no solution to the system of equations.
Thus, the correct answer is: C. There is no solution.